Strategi Otentikasi Dokumen Pada Email Menggunakan Digital Signature dengan Algoritma Schnorr - Lisda Juliana Pangaribuan; Catra Indra Cahyadi; Jaidup Banjarnahor; Berlin Barus; Bertha N Siahaan (STMIK Budi Darma, 2023)
Email is an internet facility for sending electronic mail. Although there is a webmail that provides standard security but for e-mail attachment documents when sending e-mail there are lots of eavesdropping, forgery, infiltration,and spamming so needed security of email. Authentication is identification carried out by each communicating party so sender and recipient of information trust each other. Although message authentication has been carried out, it is still possible for both parties to attack each other. This study aims to apply digital signatures in testing the integrity and authentication of document attachments email using the schnorr algorithm. SHA-1 hash function is used for verification, Results show that contents of email attachment will produce a different Message Digest if prime numbers are different, so cryptanalysts can’t solve it. Differences in Message Digest occur because different prime numbers cause differences in private keys and public keys. Private key and public key pairs are synchronous so sender and recipient are verified correctly. If there are changes or removed just one character from contents of document will result in a very significant Message Digest change. If someone changes contents of document or key, so verification process to be incorrect and recipient of information knows that document he received is no longer valid. Schnorr method is a strategy to provide document attachment security in emails that is better than security applied to standard emails